ANALISIS YURIDIS TANGGUNG JAWAB PERUSAHAAN PENYELENGGARA IBADAH UMROH TERHADAP JAMAAHNYA (STUDI PADA PT. MAKKAH WAL MADINAH TOUR CABANG MEDAN) - NUR AFRILA (PREMISE LAW JURNAL, 2016)
In umroh (lesser pilgrimage to Mecca), various kinds of fraud or manipulation is usually done by ticket or visa agents or brokers so that the aspirant pilgrims cannot get their tickets or visas according to the schedule and there  is no written contract between umroh organizers and aspirant umroh pilgrims. Actually, a written contract is regulated and stipulated in Article 45 of Law No. 13/2008 on Organizing Haj Pilgrimage to Mecca. Some conclusions of the research about the responsibility of umroh organizer were as follows: the responsibility of umroh organizer is based on law of obligations which is regulated in Article 1320 of the Civil Code and in Article 45 of Law No. 13/2008 on Organizing Haj Pilgrimage to Mecca, legal consequence of the default of umroh organizer by the absence of written contract is by imposing administrative sanction by compensating the financial loss of the aspirant umroh pilgrims and, the implementation of the contract between umroh organizer and aspirant umroh pilgrims is based on oral agreement with no written record so that the settlement of the dispute is based on three conditions: before the journey, the journey itself, the implementation of the umroh, and the journey after the umroh. It is recommended that aspirant umroh pilgrims actively search for information about umroh travel agency. Umroh organizer should make written contract with aspirant umroh pilgrims, and the government, particularly the Ministry of Religious Affairs, coordinate with the embassy of Saudi Arabia in Indonesia to control umroh organizing agencies. Keywords: Responsibility, Umroh Organizing Agency, Umroh Pilgrims